1962
DOI: 10.1017/s0003356100034486
|View full text |Cite
|
Sign up to set email alerts
|

Response to selection for multiple births in the Australian Merino: a progress report

Abstract: Results of two-way selection for multiple births are reported, in a flock of Australian Merinos.Base ewes, selected for having multiple or single births at each of two lambings at 5 and 6 years of age have shown a good repeatability, the T group (multiple-bearers) having averaged 31 more lambs per 100 ewes mated than the O group (single-bearers) for 6 subsequent lambings.Unselected daughters of the base ewes, now ranging in age from 2 to 6 years, have also shown a difference in lamb drop, those in the T group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In this respect they are similar to most previous estimates reported in the literature and reviewed by Turner et al (1962). In this respect they are similar to most previous estimates reported in the literature and reviewed by Turner et al (1962).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this respect they are similar to most previous estimates reported in the literature and reviewed by Turner et al (1962). In this respect they are similar to most previous estimates reported in the literature and reviewed by Turner et al (1962).…”
Section: Discussionsupporting
confidence: 92%
“…Estimates of heritability of numbers of lambs born in sheep have recently been reviewed by Young, Turner and Dolling (1963) and Turner et al (1962). In sheep, as in other livestock, this character is also of economic importance and consequently may be subject to some artificial selection.…”
Section: Arc Animal Breeding Research Organisation Edinburghmentioning
confidence: 99%
“…The response has been described by Turner et al (1962) and Turner (1966Turner ( , 1968Turner ( , 1969 in Peppin Merinos in which the difference in lambing rate appears to be due primarily to a correlated response in natural ovulation rate. Mean differences between groups selected for and against multiple births vary from 0·4 to 0·9 corpus luteum for ewes of various ages (Packham and Triffitt 1966;Bindon et al 1971;Trounson and Moore 1972).…”
Section: Introductionmentioning
confidence: 92%
“…The lambs used in this study were progeny of the Peppin Merino selection groups described by Turner et al (1962). Selection had either been for (T group) or against (0 group) the incidence of multiple births.…”
Section: Animalsmentioning
confidence: 99%
“…Several authors (4,8,11,Zl) reported that the sire had little or no effect on litter size, while others (t,2,9, lO, 1.2, 14) reported a ,significant sire efiect. Sire influences on litter size have been shown in mice (5, 6;13) and sheep (18,20). In cattle, a direct eftect of the sire on bfuth rate has been reported (7).…”
Section: Introductionmentioning
confidence: 99%